1986
DOI: 10.1093/infdis/154.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Vaccine-Related Immunity to Streptococcus pneumoniae

Abstract: To investigate the protective effects of pneumococcal vaccine, we assayed serum from healthy adults and from elderly bronchitics for antibody and opsonic activity against nine serotypes of S. pneumoniae. Before vaccination, there was no relation between opsonization and the level of antibody measured by RIA. Some serotypes were well opsonized in the absence of detectable antibody to capsular polysaccharide; others were not, despite modest levels of antibody. These in vitro studies did not support the concept t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0
5

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(98 citation statements)
references
References 70 publications
3
90
0
5
Order By: Relevance
“…In one study of humans, no correlation was found between opsonization and antibody levels in unimmunized adults. After immunization, most sera had increased antibody titers and opsonic activity, but a lack of correlation persisted for individual sera (37). In another study, IgG2 antibodies correlated better with opsonic activity than IgG1 antibodies (24).…”
Section: Discussionmentioning
confidence: 94%
“…In one study of humans, no correlation was found between opsonization and antibody levels in unimmunized adults. After immunization, most sera had increased antibody titers and opsonic activity, but a lack of correlation persisted for individual sera (37). In another study, IgG2 antibodies correlated better with opsonic activity than IgG1 antibodies (24).…”
Section: Discussionmentioning
confidence: 94%
“…Aged mice and elderly humans both are highly susceptible to infection with SPn (19)(20)(21)(22). In aged mice, T15-id ϩ Abs no longer dominate the immune response to SPn, and they produce anti-PC Abs that use H chains other than V H 1 and L chains other than V 22 (21,23,24).…”
Section: P Hosphocholine (Pc) Is the Immunodominant Epitope Foundmentioning
confidence: 99%
“…Since antibodies to pneumococcal capsular polysaccharide (PPS) and its complement provide protection against S. pneumoniae with homologous or cross-reactive capsular serotypes [10], pnemococcal polysaccharide vaccine (PV) is effective for preventing invasive pneumococcal diseases in patients with chronic illness, such as CLD. PV is, therefore, recommended for these patients [11][12][13].…”
Section: Introductionmentioning
confidence: 99%